Various Egusi Melon Seeds existing in Southwestern Nigerian Markets (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
Egusi is a common name for oil rich seeds of Egusi melon used mainly as soup condiment. The medium sized usually comes to mind anytime the name egusi is mentioned. But there exists a variety of crops in family Cucurbitaceae used for same purpose which is not commonly known even among the elites in Crop Science in Nigeria and beyond. In the course of a research on egusi, different types of seed forms were identified. There were six different types of egusi kernels (bojuri, itoo, serewe, igbaa, bara and wewe) based on size, colour and type sold in Nigerian markets; however, bara and serewe were the most common types of egusi found in Nigeria.
Keywords: Egusi kernels; Seed type; Seed; Colour; Seed size